2022
DOI: 10.1007/s11469-022-00815-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Exercise Addiction During the Covid-19 Pandemic in Italy

Abstract: Severe restrictive measures were implemented globally to limit the spread of the Covid-19 pandemic leading to significant lifestyle changes and impacting on both the physical and the mental health of citizens. Caught by the fear of getting sick, some individuals have adopted behaviors which favored the development of exercise addiction (EA). Our aim was to evaluate physical activity habits and the risk of EA in the general Italian population during phase 1 of the lockdown. The role of appearance anxiety (AA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the study suggests that it underlines the link between craving and quality of life, defined as the perception that the individual has regarding the effects that an illness, and its treatment, have on his physical, emotional, and social well-being. The authors indicate, in conclusion, the need to improve the quality of life, for example, through physical exercise can play an important role in reducing craving and, therefore, abusive behaviors, relapses, and abandonment of treatment [48].…”
Section: Bereavement and Psychological Pathwaysmentioning
confidence: 89%
“…Furthermore, the study suggests that it underlines the link between craving and quality of life, defined as the perception that the individual has regarding the effects that an illness, and its treatment, have on his physical, emotional, and social well-being. The authors indicate, in conclusion, the need to improve the quality of life, for example, through physical exercise can play an important role in reducing craving and, therefore, abusive behaviors, relapses, and abandonment of treatment [48].…”
Section: Bereavement and Psychological Pathwaysmentioning
confidence: 89%
“…Furthermore, De la Vega and colleagues [ 15 ], in a sample of adults from different countries (Argentina, Chile, Costa Rica, Ecuador, Honduras, Mexico, Spain, and Uruguay), found that, during the pandemic, 15.2% of the subjects were at risk of addiction and 79.6% were symptomatic of EA. In a study conducted on a sample of Italian sporty adults during the first phase of the pandemic (April–May 2020), Ceci and colleagues [ 46 ] found that the rate of EA was 4.1%. To our knowledge, no previous data about the prevalence of EA during the second wave of the COVID-19 pandemic among Italian sporty people has been published yet.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mediating habits may increase self-compassion. In addition, Ceci et al [8] conducted a survey on physical activity and exercise addiction across Italy from April to May 2020, when the strict lockdown was performed due to the COVID-19 pandemic. One instrument used was the Self-Compassion Scale (SCS), which assesses how participants usually think and/or behave to themselves through hardships.…”
Section: Introductionmentioning
confidence: 99%
“…One instrument used was the Self-Compassion Scale (SCS), which assesses how participants usually think and/or behave to themselves through hardships. Ceci et al [8] investigated 953 participants and found that the physically active group had higher SCS scores, whereas lower SCS scores predicted exercise addiction. These findings indicate that self-compassion may be associated with appropriate physical exercise habits.…”
Section: Introductionmentioning
confidence: 99%